2023
DOI: 10.28991/esj-2023-07-02-023
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics and Auditing: A Review and Synthesis of Literature

Abstract: The use of data analytics in auditing is increasingly growing. The application of common data analytics to audit engagements appears to be lagging behind other areas of practice, even though data analytics is thought to represent the future of audit, and there are still few publications that have examined this influence. This article reviews data analytics in audits and its potential for future audit engagements to describe the evolution of this research trend and picture its future growth directions. Future a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Recently, Hezam et al(2023) reviewed the literature on the use of BD and BDA in auditing. The study concluded that BDA is a promising technology that can significantly improve the effectiveness of auditing.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hezam et al(2023) reviewed the literature on the use of BD and BDA in auditing. The study concluded that BDA is a promising technology that can significantly improve the effectiveness of auditing.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…BD has the potential to revolutionize many industries, as it plays a double-edged sword that BD can be used to discover hidden patterns and insights that were previously unknown, adopt modern tools in the auditing process, and thus achieve the required speed in implementing auditing procedures effectively with high quality, cost savings, time savings (Hezam et al, 2023).On the other side, it is considered a challenge because auditing faces some problems such as data acquisition, information overload, pattern recognition, information relevance, ambiguity, privacy, and security concerns, as data can be sensitive and significant Lee, 2017;Vanbutsele,2018).…”
Section: Introductionmentioning
confidence: 99%